(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
There are many real-time situations which can be effectively solved by optimizing the basics of linear algebra by infusing it through latest AI models. This research paper is intended to bring into use the basic concepts of linear algebra along with the nuances of AI/ML to bring about optimization for solving supply chain scenario across industry. The challenge lies in Modeling disruptions (e.g., geopolitical events, pandemics) across global supply chains in real time. Linear Algebra’s Role lies in Matrix representations of supplier–buyer networks, eigenvalue analysis for systemic risk. The frontier lies in combining linear algebra with adaptive AI (reinforcement learning, quantum ML, and multi-agent systems).